Immobilization of lipases on glyoxyl–octyl supports: Improved stability and reactivation strategies. Issue 8 (August 2015) - Suescun, Angélica; Rueda, Nazzoly; dos Santos, Jose C.S.; Castillo, John J.; Ortiz, Claudia; Torres, Rodrigo; Barbosa, Oveimar; Fernandez-Lafuente, Roberto
Graphical abstract